Ten-month-old infants’ neural tracking of naturalistic speech is not facilitated by the speaker’s eye gaze - Melis Çetinçelik; Caroline F. Rowland; Tineke M. Snijders (Developmental Cognitive Neuroscience, 2023)
Eye gaze is a powerful ostensive cue in infant-caregiver interactions, with demonstrable effects on language acquisition. While the link between gaze following and later vocabulary is well-established, the effects of eye gaze on other aspects of language, such as speech processing, are less clear. In this EEG study, we examined the effects of the speaker’s eye gaze on ten-month-old infants’ neural tracking of naturalistic audiovisual speech, a marker for successful speech processing. Infants watched videos of a speaker telling stories, addressing the infant with direct or averted eye gaze. We assessed infants’ speech-brain coherence at stress (1–1.75 Hz) and syllable (2.5–3.5 Hz) rates, tested for differences in attention by comparing looking times and EEG theta power in the two conditions, and investigated whether neural tracking predicts later vocabulary. Our results showed that infants’ brains tracked the speech rhythm both at the stress and syllable rates, and that infants’ neural tracking at the syllable rate predicted later vocabulary. However, speech-brain coherence did not significantly differ between direct and averted gaze conditions and infants did not show greater attention to direct gaze. Overall, our results suggest significant neural tracking at ten months, related to vocabulary development, but not modulated by speaker’s gaze.